Efforts To Handle Waste Management Through Clean Village Program Planning In Improving Environmental Quality (Case Study Of Batang Kuis District) - Dimas Setiawan; Wahyu Hidayat (Yayasan Sinergi Multidimensi Kreatif, 2025)
The environment is one of the factors that support the sustainability of human life. To meet the conditions of people who live healthy and prosperous in the future, it is necessary to have a healthy residential environment that avoids waste. This study aims to find out the condition of waste management in Batang Kuis District, to find out the role of the government and related parties in supporting effective waste management in Batang Kuis District, and to find out the efforts to handle waste management through the planning of a clean village program in improving environmental quality in Batang Kuis District. The method used in this study is a qualitative method with a descriptive approach. Data collection techniques are in the form of observation, interviews and documentation. The results of the study show that (1) The condition of waste management in Batang Kuis District shows several positive developments, although it is still faced with a number of challenges. Waste management in this sub-district is carried out through three main stages including collection, transportation, and disposal to the final disposal site (TPA). (2) The role of the Government and related parties in supporting effective waste management in Batang Kuis District by taking strategic steps, namely providing a fleet of waste transporters and building a more organized temporary disposal site (TPS), to facilitate the process of collecting and transporting waste. In addition, the government's involvement in educating the public, especially the younger generation, through educational programs. (3) Efforts to handle waste management through the planning of the clean village program in improving environmental quality in Batang Kuis District include training in waste sorting, composting, and the establishment of a waste bank. This program has succeeded in creating positive changes in residents' habits, especially in sorting waste and utilizing waste productively.